HUBUNGAN LAMA PAPARAN POLUSI UDARA DAN PERILAKU MEROKOK TERHA¬DAP FUNGSI PARU PADA DRIVER OJEK ONLINE - Monica, Monica; Suwarno, Maria Lousiana; Hidayah, Ainum Jhariyah (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
Increasing levels of air pollution in Jakarta will have serious health impacts for those exposed, such as online motorcycle taxi drivers. Smoking behavior by online motorcycle taxi drivers can also cause health problems in the form of decreased lung function. This research aimed to figure the relationship between duration of exposure to air pollution and smoking behavior to lung function in online motorcycle taxi drivers at Jakarta. This research used a descriptive correlation design with cross-sectional approach which conducted in June-July 2020. There were 106 online motorcycle taxi drivers selected using accidental sampling technique. Lung function measured using the mMRC dyspnoe scale and distributed using google form. The results of this study found that the mostly 97,7% online motorcycle taxi drivers worked > 40 hours/ week, 68,9% online motorcycle taxi drivers categorized of mild smoking, 60,4% online motorcycle taxi drivers had no dyspnea symptoms (grade 0). Statistical analysis using chi-square showed that there is a significant relationship between smoking behavior with lung function (p-value 0,001), however, there is no significant relationship between duration of exposure to air pollution with lung function (p-value 0,056). It’s expected that online motorcycle taxi drivers can use masks while working to reduce exposure to air pollution and lesser to quit smoking.